Epigenetics: a historical overview - Holliday, Robin (Henry Stewart Talks, 2007)
Introduction to epigenetics, the leading pioneers in the field of epigenetics, the basic features of development, switching and heritability of gene activities, DNA methylation, epimutations, differences between genetics and epigenetics, genomic imprinting, chromatin structure, histone modifications, the role of RNA in the epigenetic regulation of gene activity, the bisulfite sequencing technique, the epigenotype
Reviewed at 2020/08/12, Archived at 2020/10/21